Poefica Theologica: Donne and Hopkins in the PatristicHumanistic Tradition of Theology - Davidson, Andrew (My University, 2008)
In this study, I have argued that John Donne's Devotions Upon Eillergent Occasions ( 1624) and Gerard Manley Hopkins' The Wreck of the Deutschland ( 1918) are not simply forms of devotional literature or spiritual autobiography, but constitute works of theology in their own right. From a contemporary perspective, such a claim may seem to entail a gratuitous revisioning of the theological tradition, but I mean it as a hermeneutic retrieval. It is often assumed in scholarly circles that logic and the dialogical arts have always been the natural allies of theology. As a result, the Devotions and The Wreck are typically viewed as supplemental to theological study; they are "soft" literary works that serve to exemplify the "hard" truths of scholastic divinity and sectarian dogma. My claim is that the Devotions and The Wreck are theological in the classic sense precisely because they are literary and devotional, spiritual and autobiographical. Donne and Hopkins are poet theologians writing in a patristic-humanistic strain of the theological tradition. Instead of giving priority to the logical-dialectical orientation of systematic theologians and modern philosophers-whether in affirmation of or resistance to sllch an orientation-they follow the example of church fathers like Origen and Augustine and Christian humanists like Erasmus and Valla by treating matters of divinity in a distinctly literary, existential, and dramatistic manner. To be more specific, they seek to tell the truth at the lively intersection of exegesis and poesis, engaging an inventive hermeneutic set within the bounds of authority and tradition so as to participate responsively in divine re-creation.
Keywords: Poetica Theologica; theology; English Language and Literature; English Language and Literature